Dinamika Kampung-kampung Tua di Sekitar Gunung Rajabasa, Lampung Selatan - Mang Nanang; Endang Widyastuti; Iwan Hermawan (Badan Riset dan Inovasi Nasional (BRIN), 2024)
Settlement is a form of human culture that is dynamic. The journey of a settlement begins from its formation to its development. In its development, some settlements have been displaced. As a result of the move, the abandoned old village will experience setbacks and destruction. Several theories about settlements state that the displacement of a settlement is caused by natural factors, namely the decline in quality so that it does not meet human needs, and there are also natural disasters. In addition to natural factors, the movement of settlements is also caused by cultural factors, such as the ruler's decision or ease of interaction between communities. During the White Blood Era in Lampung, settlements developed around Mount Rajabasa. These settlements have experienced dynamics until now. This study discusses the pattern of old villages around Mount Rajabasa and what causes these old villages to experience dynamics in the form of displacement. The research method applies a qualitative research type. Data was collected through observation and accompanied by interviews and literature studies. Several old village sites were found and moved to villages that can now be found. Ecological, political, and transportation factors influence displacement.